2010
DOI: 10.1577/h09-004.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Distribution of Bacterial Flora in Farmed Rainbow Trout from Mexico

Abstract: Trout farming is a growing aquaculture industry in Mexico, with stock mainly supplied by the importation of eyed eggs. The aim of the present study was to determine the frequency of bacterial isolations in farmed rainbow trout Oncorhynchus mykiss from Mexico. Sixty-five farms distributed among seven states of Mexico were included in the study. Individual samples from gills, liver, spleen, intestine, and kidney were obtained from 563 apparently healthy fish. In total, 371 bacterial isolates were recovered from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 7 publications
1
13
1
3
Order By: Relevance
“…To this end, we analysed 253 whitefish samples from five lakes and identified an unprecedented number of bacterial genera in kidneys, including 579 different genera among which 10 were pathogenic bacterial genera that comprised 18 known pathogenic species. This contrasts with previous studies that considered kidneys to be a sterile organ in healthy fish (Goldschmidt‐Clermont et al ., ; Dionne et al ., ; Salgado‐Miranda et al ., ). Of course, one must consider that contamination could partly explain the level of bacterial diversity observed in whitefish kidneys.…”
Section: Discussionmentioning
confidence: 97%
“…To this end, we analysed 253 whitefish samples from five lakes and identified an unprecedented number of bacterial genera in kidneys, including 579 different genera among which 10 were pathogenic bacterial genera that comprised 18 known pathogenic species. This contrasts with previous studies that considered kidneys to be a sterile organ in healthy fish (Goldschmidt‐Clermont et al ., ; Dionne et al ., ; Salgado‐Miranda et al ., ). Of course, one must consider that contamination could partly explain the level of bacterial diversity observed in whitefish kidneys.…”
Section: Discussionmentioning
confidence: 97%
“…fluorescens being one of them [70]. However Pseudomonas species have been identified as members of autochtonous microbiota of farmed fish [71][72][73][74], and several authors have reported the potential probiotic role play for strains of Pseudomonas genus [8,71,75,76].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of freshwater species harbor plesiomonads. In addition to those fish cited in a previous review (28), recent investigations have isolated Plesiomonas from rainbow trout (53,54), carp (55), and tilapia (44,56,57). Studies of the intestinal tracts of a number of freshwater fish suggest that the genus Plesiomonas is one of the most common species composing the bacterial microbiota of these vertebrates, in addition to Fusobacterium and Aeromonas (58,59).…”
Section: Invertebrate and Vertebrate Hostsmentioning
confidence: 99%